ВОЛКОЛАК: ОТ ЧУЖДОГО К ЧУДЕСНОМУ - Czerniawska, Julia (Acta Neophilologica, 2005)
This article presents research for the character of the volkolak (Verwolf in German) as one of the most universal and simultaneously mystic personages of lower demonology. Author rises the question about reason of such character’s ambivalence as in wide sense („strong” and „weak” volkolaks which the people’s attitude differs to in various cultures) as in narrow sense (brutish-human volko- lak’s nature). The volkolak’s character thus personifies contradictary relationship to „own alien”. Being personified in characters of prince, shaman, chieftain, the dual volkolak’s nature is welcomed as a personification of supernatural powers of supreme figure as well as a group presented by this figure. In tum, „volkolak neighbour” is presumably belonged to a social, ethnic or confessional minority; it shares its community life from one hand, and visibly differs from another community members from the other. While observing such analogies as ‘volkolak wolf, ‘volkolak dead’, ‘volkolak being initiated’ etc, the author defines transitivity and marginality as the main core of the personage. Main advantage of the ‘weak’ volkolak is possibility of union to the Marvellous as being different from the Own and supernatural that is giving a loose out of routine framework. The author promotes potential of volkolak as a personage that is rising under modem conditions of polystilism.